(untitled) (Journal of Health Sciences, 2022)
Introduction: Studies of dental practitioners performed around the world demonstrate that COVID-19 pandemic negatively impacts their daily activities lives, social functions, and health-care providing duties. The aim of the study is to evaluate the pandemic-induced psychological stress and associated factors on dental academics in Iraq.Methods: We conduct an observational study using a self-administered survey to obtain data from dental academics in many colleges of dentistry within Baghdad city. A closed-ended questionnaire was utilized, to assess post-traumatic responses to particular events. The Impact of Event Scale was used to assess the level of stress in the first of two outcomes. The second depicts the effects of COVID-19 on behavioral changes.Results: A total of 108 participants from seven colleges in Bagdad responded. About 38% reported a state of severe stress, 46.3% showed moderate stress, and 13.9% complained of mild states of stress. Stress levels were found to be substantially linked to fear of infection, worries about professional responsibilities, and limited mobility.Conclusion: The pandemic stress induces psychological and behavioral changes on the Iraqi dental educators, which can never be eliminated.